Open-loop Zero-sum Linear Quadratic Dynamic Game for Descriptor System - Salmah, (2009)
Linear quadratic continuous zero-sum 2 player dynamic game with descriptor system will be defined. The assumption for the game is open-loop. Optimization problem in the Nash sense will be constructed. Based on the result of non-zero-sum linear quadratic game for descriptor system, Riccati type differential equation will be considered. The connection of game problem solution and Riccati equation will be studied for fonite time and infinite time problem.